(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This research focuses on the functions of project management, warehousing, asset management, and procurement in Hospital Logistics Part 1. The system needs to monitor and manage the different parts of a logistics transaction in a hospital for the user to be more productive and have a reliable outcome and analysis. This system is for providing more accurate and reliable data about the transactions in the logistics part 1 of the hospital. The main objective of this system is to provide efficiency in managing and monitoring the logistics of the hospital’s part 1 transaction. As a result, the researcher found out that the development of a reliable and efficient system for managing logistics in hospitals is of great importance in ensuring the smooth flow of resources and supplies, which is essential for providing high-quality healthcare services. The involvement of stakeholders and the use of daily standup meetings help to ensure that the system is designed and implemented to meet the needs of those who will use it. The researcher produces a system that can manage and monitor the transaction in logistics part 1 of the hospital. This system helps the hospital to manage and monitor the transactions in the logistics part 1 of the hospital. The system can improve the user’s productivity and give them efficiency in their work. The system can also ensure the security of the data and information input into it.